Refleksi Metafisik Atas Teks Serat Kaca Wirangi - Sudaryanto Sudaryanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
Serat Kacawirangi is a symbolic tale, its content of the grace and perfection of human life. This doctrine has the Javanese religio-magic concept and Islamic background. It has a monistic-spiritualistic metaphysical view. The ultimate reality did not find in the temporal and variable experiences. The experience is an image if the ultimate reality, so it is the pseudo reality. The ultimate reality likes a mirror. It is dominated by the light, without color and properties; but it capable of being of all property and color. Human perfection be able to find if life more spiritualistic, likes the mirror that is dominated by the light (reason), without color (escaped from the passion); so they are able to receive the pluralistic of human experiences that colored by good and bad characterstic.